Evidence-based practice in optometry: are the knowledge carried forward by students after graduation? - Zainora Mohammed; Norliza Mohamad Fadzil; Mohd. ‘Izzuddin Hairol; Sumithira Narayansamy; Mizhanim Mohamad Shahimin; Bashirah Ishak; Norlaila Md Daud; Sharanjeet Kaur; Noor Shahida Sukiman (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aim of this study is to explore the perceived benefit of Evidence-based practice (EBP) as teaching and learning approaches in undergraduate optometry program. The perceived benefit of EBP was measured using Taipei Evidence-Based Practice Questionnaire (TEBPQ). TEBPQ consists of 26 self-reported items, which include domains of ‘Ask’, ‘Acquire”, ‘Appraisal’, ‘Apply’ and ‘Attitude’. The questionnaire was administered to two cohorts of Optometry students. Thirteen students in cohort 2018/2019 (new graduates) and 35 students in cohort 2019/2020 (ongoing training) completed the questionnaire. The highest score for students in cohort 2018/2019 was for ‘Ask’ domain (3.26±0.41) and the lowest score was for ‘Apply’ domain (3.05±0.57). The highest score for students in cohort 2019/2020 was for ‘Ask’ domain (3.22±0.35) and the lowest score is ‘Appraisal’ domain (3.02±0.41).However, two-samples Mann-Whitney U test showed no significant difference for all four domains in EBP between the two cohorts (p>0.05). ‘Attitude’ domain also showed no significant difference between the two cohorts (p>0.05). In this study, both cohorts of optometry students showed equal EBP related knowledge and they have good attitude towards the importance of EBP competencies in clinical decision making.